Structural Derivatization of Clusianone and In Vitro Cytotoxicity Evaluation Targeting Respiratory Carcinoma Cells - Nagalingam, Sree Vaneesa; Wai-Ling, Kok; Teng-Jin, Khoo (Planta Medica Letters, 2016)
Clusianone (1) was isolated from Garcinia parvifolia and structurally modified using semisynthetic methods to obtain compounds 2–4. The structural derivatization included methylation (2), hydrogenation (3), and the addition of a methylamine group [(4) to (1)]. Cytotoxic effects of these compounds were assessed on MRC5 fibroblasts, A549 lung adenocarcinoma, HK1 squamous nasopharynx carcinoma, and NP69 normal nasopharyngeal epithelial cell lines. Clusianone (1) showed cytotoxic activity against A549 cells with an IC50 value of 3.06 µM. Compound (4) showed cytotoxic activities against both A549 and HK1 cells with IC50 values of 4.09 µM and 3.43 µM, respectively. The results of the cytotoxicity assay provide a correlation on the structure activity relationship of clusianone against HK1 and A549 cells, which can be further investigated as a potential antiproliferative compound.
Keywords: Garcinia parvifolia; Clusiaceae; clusianone analogues; semisynthetic methods; cytotoxic activity